Discussion on “Applying fuzzy theory and genetic algorithm to interpolate precipitation” by C.L. Chang, S.L. Lo, and S.L. Yu - Şen, Zekai (Elsevier BV, 2006)
Summary Unfortunately, the present paper has many scientific mistakes even in the basic conception and application of the fuzzy theory and genetic algorithm applications in addition to the inverse distance weighting (IDW) method approach. For instance, although in the abstract the authors state that “… combining the inverse distance method and fuzzy theory…”, in fact one of their misconceptions is that they regard the weighting factors in the IDW interpolation method and the membership function in the fuzzy theory to be same but have expressed in different words. This statement indicates that the authors arrived at such a conclusion on the basis of geometrical similarity between the weighting factors and membership functions, which is not valid.